Mitigation of Voltage Dip and Voltage Flickering by Multilevel D-STATCOM. (14th October 2012) - Ballal, M. S.; Suryawanshi, H. M.; Venkateswara Reddy, T.
Abstract : The basic power quality problems in the distribution network are voltage sag (dip), voltage flickering, and the service interruptions. STATCOM is a Flexible AC Transmission Systems (FACTS) technology device which can independently control the flow of reactive power. This paper presents the simulation and analysis of a STATCOM for voltage dip and voltage flickering mitigation. Simulations are carried out in MATLAB/Simulink to validate the performance of the STATCOM. A comparison between the six-pulse inverter and the five-level diode-clamped inverter is carried out for the performance of 66/11 KV distribution system.